ANALISIS KARAKTERISTIK HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN MENGATASI PREMENSTRUASI SINDROM - Tiffani Tantina (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
Premenstrual syndrome is quite high, with almost (75%) of women of childbearing age around the world experiencing premenstrual syndrome. Country of Indonesia itself the number of events around (70-90%), which occurs in women of childbearing age and more often found in women aged 20-40 years. This figure indicates that Premenstrual Syndrome in Indonesia is quite a lot that needs to be done countermeasures to stay and overcome it. Low knowledge of the various forms of adolescents have risky behavior / action. The purpose of this study was to analyze the relationship between the variables studied and knowledge with Premenstrual Actions Syndrome. This research method uses pure quantitative in cross sectional approach. The research subjects were female teenagers residing in the new village of Pancur Batu sub-district, which faced 90 people who were 12-16 years old. Random sampling technique by simple random sampling. Data analysis was done by Chi-Square test with multiple Linear regression test. The result of the study was no correlation between end result of age, education, first menstruation with action of overcoming premenstrual syndrome ,the most dominant and significant variable is age,and knowledge also has a significant relationship with the action of overcoming premenstrual syndrome.